Parametric optimization of the output shaft of a portal axle using finite element analysis - Ooi, Jong Boon (Strojniški vestnik, 2013)
A portal axle unit is a gearbox unit installed on a vehicle for higher ground clearance and driving in off-road conditions. Shafts must be exceptionally tough and light to improve the overall performance of the portal axle unit. In this paper, a hollow shaft with a rib at both ends was proposed. The torsional stress of the three-dimensional shaft model was determined using finite element analysis (FEA) and validated by experimental testing. The hollow shaft thickness, rib thickness, depth of spokes, rib fillet radius, and number of spokes are the five of parameters considered in the torsional strength analysis of the rib. A Taguchi orthogonal array (L25) was applied to determine the optimum set of parameters for the proposed shaft. The strength and weight of the optimized model were calculated and compared to the solid shaft, hollow shaft, and proposed model. The optimized model showed improvement in torsional strength with a slight increase in weight compared to the benchmark model.
Keywords: finite element analysis; finite element method; metoda končnih elementov; metoda Taguchi; parametric optimization; parametrična optimizacija; portal axle; portalne preme; shaft design; votle gredi; zasnova eksperimenta; zasnova gredi